2022
DOI: 10.1002/cb.2070
|View full text |Cite
|
Sign up to set email alerts
|

Shaping customer brand loyalty during the pandemic: The role of brand credibility, value congruence, experience, identification, and engagement

Abstract: While insight into consumer brand engagement, experience, and identification is rapidly developing, little remains known regarding the association of these, and related, concepts, as therefore explored in this article. Drawing on social identity theory and service‐dominant‐logic, this study develops and tests a model that explores the effect of customers' brand credibility, ‐value congruence, and ‐experience on their brand identification, and its subsequent effect on their brand advocacy, ‐attachment, and ‐loy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 97 publications
4
52
0
8
Order By: Relevance
“…The significant positive effect of habitual purchase brands indicates that respondents are more likely to purchase egg brands that they are familiar with and purchase frequently in daily life. This finding is consistent with previous research in China [ 6 , 35 ] and many other countries [ 45 , 49 ] that trust in one brand could be accumulated over time through regular purchases.…”
Section: Empirical Analysis and Discussionsupporting
confidence: 93%
“…The significant positive effect of habitual purchase brands indicates that respondents are more likely to purchase egg brands that they are familiar with and purchase frequently in daily life. This finding is consistent with previous research in China [ 6 , 35 ] and many other countries [ 45 , 49 ] that trust in one brand could be accumulated over time through regular purchases.…”
Section: Empirical Analysis and Discussionsupporting
confidence: 93%
“…This finding is in line with the previous findings. Past studies also found that credibility on brand creates higher levels of customer loyalty (Alam et al, 2012;Rather et al, 2022). Moreover, Hypothesis six investigated the mediation effect of unverified information sharing between credibility and loyalty.…”
Section: Discussionmentioning
confidence: 88%
“…Other recent study found that credibility have significant positive effect on customers' brand identification which in turn positively effect loyalty. (Rather et al, 2022).Thus, loyalty plays an important role in shaping a positive relationship between consumers and companies. In this study, the loyalty factor refers to customer loyalty gained from SMEs through their blog posts.…”
Section: Promotional Incentivesmentioning
confidence: 99%
“…Relatedly, while the TPB suggests that consumers' behavioral intent is directly affected by their PBC (Ajzen, 1991;Hollebeek et al, 2022a), as the present SDC-based findings corroborate, consumers' level of SDC engagement is also found to mediate this association. That is, PBC exhibits both a direct and indirect effect on the user's intent to purchase an SDC (i.e., as mediated via engagement), revealing more nuanced insight into these dynamics (Rather et al, 2022;Villagra et al, 2021). This result makes sense, as the higher one's perceived control when driving an SDC, the greater one's expected (e.g., cognitive/behavioral) resource investment in interacting with the SDC, thus boosting the individual's SDC engagement (Kumar et al, 2019;Hollebeek et al, 2019).…”
Section: Theoretical Implicationsmentioning
confidence: 99%